2016
DOI: 10.1093/protein/gzw037
|View full text |Cite
|
Sign up to set email alerts
|

TetraMabs: simultaneous targeting of four oncogenic receptor tyrosine kinases for tumor growth inhibition in heterogeneous tumor cell populations

Abstract: Monoclonal antibody-based targeted tumor therapy has greatly improved treatment options for patients. Antibodies against oncogenic receptor tyrosine kinases (RTKs), especially the ErbB receptor family, are prominent examples. However, long-term efficacy of such antibodies is limited by resistance mechanisms. Tumor evasion by a priori or acquired activation of other kinases is often causative for this phenomenon. These findings led to an increasing number of combination approaches either within a protein family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…2, box 8 ). 196 The scFab format was also combined with the LUZ-Y Fc heterodmerization strategy ( Fig. 2, box 7 ).…”
Section: Bispecific Iggs With Asymmetric Architecturementioning
confidence: 99%
“…2, box 8 ). 196 The scFab format was also combined with the LUZ-Y Fc heterodmerization strategy ( Fig. 2, box 7 ).…”
Section: Bispecific Iggs With Asymmetric Architecturementioning
confidence: 99%
“…At present, the most effective chemotherapeutic drugs for NSCLC are gefitinib, erlotinib, and afatinib, which are highly targeted EGFR-directed tyrosine kinase inhibitors (TKIs) [ 4 ]. However, genetic instability, aberrant activation of signaling pathways, and development of secondary drug resistance have become the major limitations of such drugs [ 5 ]. Exploring novel therapeutic agents with promising anticancer activity and their molecular mechanisms is, therefore, necessary for improving the outcome of NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the superiority of a tetraspecific antibody to individual monospecific antibodies was demonstrated in a heterogenous tumour population. (200) Beyond inducing antibody dependent cell cytotoxicity by recruiting FcγR positive immune cells, some research groups have looked at targeting the immune system against cancer by designing dual antibody constructs that cross-link tumour cells and T cells via their CD3 receptors. (199) In terms of the ErbB family specifically, where the HER2 receptor is completely dependent and the HER3 is a partially impaired RTK, preventing heterodimerisation is a key strategy.…”
Section: Her2 Does Not Play a Significant Role In Perineural Spread Omentioning
confidence: 99%
“…Furthermore, comparable to dual EGFR/HER2 targeting, several studies have now shown that dual inhibition of HER3 and EGFR is efficacious in multiple tumour models. (200) Moreover, inhibition of HER3 phosphorylation has been correlated with anti-proliferative activity of tyrosine kinase inhibitors in colorectal, pancreatic and NSCLC cell lines, suggesting that optimal EGFR signalling inhibition requires simultaneous inhibition of HER3 signalling. (210) We were unfortunately unsuccessful in our initial attempts to optimise a HER3 immunostaining protocol for FFPE tissue to allow assessment of HER3 expression in perineural spread cSCCHN.…”
Section: Her2 Does Not Play a Significant Role In Perineural Spread Omentioning
confidence: 99%